Chemical profiling and assessment of immunomodulatory properties of Terminalia catappa linn and Terminalia subspathulata king on red hybrid tilapia (Oreochromis sp.) - Yakubu, Yahaya (2020)
Fish farming is a rapidly growing venture throughout the globe. This is due to the revenue it generates and the lesser health risk it poses to humans upon consumption. However, they are faced with pathogens and disease outbreaks. Although treatment with antibiotics and prevention with vaccines are still effective but have their attendant challenges, as such, they are gradually giving way to natural plant-based therapy, which is believed to have lesser to negligible side effects for preventing these diseases outbreaks. One of such plant whose leaf is traditionally used by fish farmers to prevent disease outbreak or boost the immunity of fish is the Terminalia catappa (Ketapang). Terminalia catappa (TC) belongs to the Terminalia species (TS), which are phytotherapeutic plants with over 200 known species but having only very few explored. The traditional uses of some of the explored species like Terminalia catappa have not been scientifically proven to leave them as a myth. On the other hand, Terminalia subspathulata (TST) (Jelawi Jaha), to the best of our knowledge, is one of the species of this family that is unexplored for any medicinal purpose. This research investigates the chemical profiles of the leaves, barks, nut and fruit of Terminalia catappa and Terminalia subspathulata crude extracts using ultra high performance liquid chromatography electrospray tandem mass spectrometry (UHPLC-ESIMS/ MS) and gas chromatography (GCMS) techniques, in addition, to their antioxidant potential. Furthermore, the acute toxicity, immunostimulant potential and disease resistance on red hybrid tilapia (Oreochromis sp.) model were also assayed. The UHPLC-ESI-MS/MS metabolite profiling of the leaves, bark, nut and fruit of Terminalia catappa and Terminalia subspathulata resulted in the identification of 195 metabolites, mostly phenolics and few organic acids. While the GCMS profiles of the nut and fruit of Terminalia catappa and Terminalia subspathulata revealed majorly saturated and unsaturated fatty acids. The total phenolic content (TPC) and total flavonoid content (TFC) attested to the fact that Terminalia catappa and Terminalia subspathulata have phenolic medicinal metabolites which manifested in their scavenging activities in the assessment of their antioxidant potential (AOP), using 2,2,diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant potential (FRAP) and 2,2-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assays. The acute toxicity study was conducted using the doses; 31.125 mg/kg, 62.5 mg/kg, 125 mg/kg, 250 mg/kg and 500 mg/kg. Fish were sacrificed after 96 hours, blood samples collected for analysis (complete blood haemogram and biochemistry) and five organs (gill, heart, kidney, liver and spleen) were also collected for histological assessment. From the results, toxic signs were observed from 125 mg/kg to 500 mg/kg and as such, were not used for the immunostimulant assessment. The innate immune parameters (phagocytosis, respiratory burst, lysozyme activity, and complement assay) studied using 31.125 mg /kg, 62.5 mg/kg leaf crude extracts of Terminalia catappa and Terminalia subspathulata showed an increase in the immunity of fish after two weeks in the phagocytotic, respiratory burst, lysozyme activities. This led to the partitioning of the leaf crude extracts of Terminalia catappa and Terminalia subspathulata with nhexane, chloroform, ethyl acetate and methanol to determine the most effective fraction on the aforementioned immune parameters leading to isolation of compound(s). From the immune study of the partitioned extracts, the ethyl acetate and chloroform fractions showed a more improved response in the immune parameters. Consequently, leading to the isolation of β-sitosterol, stigmasterol-3-O-β Dglucopyranoside, gallic acid and quercetin-3-O-rhamnoside from the ethyl acetate fractions of Terminalia subspathulata leaf, which happens to be an unexplored species in the genus of Terminalia species. The results prove the claim scientifically from different quarters, saying that Terminalia catappa leaf boosts the immunity of fish and has demonstrated that other species of Terminalia can also perform the same function. Furthermore, the result also reveals medicinal metabolite in Terminalia subspathulata and its biological potentials. We believe these findings will help strengthen the use of these readily available plants (Terminalia catappa and Terminalia subspathulata) as a cheaper way of boosting the health of fish against pathogens in aquaculture.